2018
DOI: 10.1063/1674-0068/31/cjcp1808192
|View full text |Cite
|
Sign up to set email alerts
|

Imaging HNCO photodissociation at 201 nm: State-to-state correlations between CO (X1Σ+) and NH (a1Δ)

Abstract: The NH(a1Δ)+CO(X1Σ+) product channel for the photodissociation of isocyanic acid (HNCO) on the first excited singlet state S1 has been investigated by means of time-sliced ion velocity map imaging technique at photolysis wavelengths around 201 nm. The CO product was detected through (2+1) resonance enhanced multiphoton ionization (REMPI). Images were obtained for CO products formed in the ground and vibrational excited state (v=0 and v=1). The energy distributions and product angular distributions were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In the past years, channel 3 has been investigated at wavelengths between 193 and 230 nm. A cold 1 NH rotational distribution together with a hot CO distribution was identified. By using the high resolution velocity map ion (VMI) imaging technique, Zhang et al , reported the pair-correlation between 1 NH and CO products at 201 nm photolysis. A bimodal rotational distribution was observed in the CO product, which was explained as resulting from the involvement of two HNCO isomers (cis and trans) in the dissociation process.…”
Section: Introductionmentioning
confidence: 99%
“…In the past years, channel 3 has been investigated at wavelengths between 193 and 230 nm. A cold 1 NH rotational distribution together with a hot CO distribution was identified. By using the high resolution velocity map ion (VMI) imaging technique, Zhang et al , reported the pair-correlation between 1 NH and CO products at 201 nm photolysis. A bimodal rotational distribution was observed in the CO product, which was explained as resulting from the involvement of two HNCO isomers (cis and trans) in the dissociation process.…”
Section: Introductionmentioning
confidence: 99%
“…Through the specific cooling and multiphoton fluorescence spectroscopy techniques, the origin of the S 1 state was measured to be located at 32449 AE 20 cm À1 . 30 Interestingly, a bimodal structure was found to appear in the distributions of the product CO (at 201 and 210 nm) 25,26 and NH (at 217.6 nm) 15 in channel (1c). Very recently, a more exquisite feature of the rotational distribution of CO(v = 0) with a trimodal structure in the dissociation dynamics of HNCO(S 1 ) was measured at 215 and 217 nm.…”
Section: (1c)mentioning
confidence: 97%
“…Photodissociation dynamics of HNCO via the S 1 state at the wavelengths longer than 201 nm has attracted much attention in experiment. 5,7,10,[15][16][17][18][19][20][21][22][23][24][25][26][27][28] The absorption spectrum, 13,29,30 product correlated distributions of the channel (1c), 15,17,22,23,25,26,28 internal energy distributions of NCO, 24,27 quantum yield of H atom, 5,16,20,21 as well as the product recoil anisotropy parameters 7,15 have been obtained by several experimental groups using various kinds of experimental techniques. The measured absorption spectrum was shown to be broad and structureless, 13 which can be ascribed to a large change of the HNCO geometries upon the photoexcitation.…”
Section: (1c)mentioning
confidence: 99%